Tumour necrosis factor (TNFα) as a novel therapeutic target in symptomatic corticosteroid dependent asthma. Issue 12 (15th September 2005) - Howarth, P H; Babu, K S; Arshad, H S; Lau, L; Buckley, M; McConnell, W; Beckett, P; Al Ali, M; Chauhan, A; Wilson, S J; Reynolds, A; Davies, D E; et al.
Abstract : Background: Tumour necrosis factor α (TNFα) is a major therapeutic target in a range of chronic inflammatory disorders characterised by a Th1 type immune response in which TNFα is generated in excess. By contrast, asthma is regarded as a Th2 type disorder, especially when associated with atopy. However, as asthma becomes more severe and chronic, it adopts additional characteristics including corticosteroid refractoriness and involvement of neutrophils suggestive of an altered inflammatory profile towards a Th1 type response, incriminating cytokines such as TNFα. Methods: TNFα levels in bronchoalveolar lavage (BAL) fluid of 26 healthy controls, 42 subjects with mild asthma and 20 with severe asthma were measured by immunoassay, and TNFα gene expression was determined in endobronchial biopsy specimens from 14 patients with mild asthma and 14 with severe asthma. The cellular localisation of TNFα was assessed by immunohistochemistry. An open label uncontrolled clinical study was then undertaken in 17 subjects with severe asthma to evaluate the effect of 12 weeks of treatment with the soluble TNFα receptor-IgG1 Fc fusion protein, etanercept. Results: TNFα levels in BAL fluid, TNFα gene expression and TNFα immunoreative cells were increased in subjects with severe corticosteroid dependent asthma. Etanercept treatment was associated with improvement in asthma symptoms, lung function, and bronchial hyperresponsiveness. Conclusions: These findings may be of clinical significance in identifying TNFα as a new therapeutic target in subjects with severe asthma. The effects of anti-TNF treatment now require confirmation in placebo controlled studies.